2000
DOI: 10.1074/jbc.m909382199
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Retinoic Acid Receptor-deficient Keratinocytes

Abstract: Vitamin A derivatives (retinoids) play central roles in embryonic development and maintenance of various tissues in the adult (1-3). Retinoids also exhibit potent antitumorigenic properties in diverse model systems and show potential for the treatment of a number of human malignancies, including diverse epithelial cancers or pre-cancerous lesions (4 -9).The retinoid signal is transduced by two families of nuclear receptors, the retinoic acid (RA) 1 receptors (RAR␣, -␤, and -␥ and their isoforms) and the retino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 70 publications
3
36
0
Order By: Relevance
“…Our results corroborate previous findings of an increased RARγ/RARα mRNA ratio in confluent human keratinocytes [37] and induction of RXRα in calcium-treated and post-confluent keratinocytes [38]. By extrapolating to the in vivo situation, RARα/RXRα heterodimers are likely to predominate in the basal layers of the epidermis while RARγ/RXRα should predominate in the suprabasal layers suggesting separate functions for RARα/γ and RXRα in keratinocyte differentiation [39]. In view of this, our results could have the following implication: The responsiveness of a tissue or cell to a hormonal factor such as RA is largely dependent on the abundance of the corresponding nuclear receptor.…”
Section: Calcium-induced Differentiation Results In Increased Retinoisupporting
confidence: 81%
See 1 more Smart Citation
“…Our results corroborate previous findings of an increased RARγ/RARα mRNA ratio in confluent human keratinocytes [37] and induction of RXRα in calcium-treated and post-confluent keratinocytes [38]. By extrapolating to the in vivo situation, RARα/RXRα heterodimers are likely to predominate in the basal layers of the epidermis while RARγ/RXRα should predominate in the suprabasal layers suggesting separate functions for RARα/γ and RXRα in keratinocyte differentiation [39]. In view of this, our results could have the following implication: The responsiveness of a tissue or cell to a hormonal factor such as RA is largely dependent on the abundance of the corresponding nuclear receptor.…”
Section: Calcium-induced Differentiation Results In Increased Retinoisupporting
confidence: 81%
“…This is supported by a report showing that RA affects different genes in keratinocytes deficient in RARα or RARγ [39]. Further studies are needed to elucidate whether a corresponding mechanism exists also in human normal keratinocytes.…”
Section: Calcium-induced Differentiation Results In Increased Retinoimentioning
confidence: 47%
“…AP-1 activity has been closely linked to epidermal tumorigenesis in vivo and cellular transformation in vitro (Jochum et al, 2001). While the basis for this effect is not fully understood, trans-repression of AP-1 has been suggested to be responsible for the growth inhibitory effects of RA in many cell types, including keratinocytes (Karin et al, 1997;Goyette et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Mouse JB6 cells express only RAR g and a, not RAR b, and the tumor promotion inhibiting activity has been attributed to the RAR g (Rudd et al, 1993). RAR g is functionally predominant for transrepression in keratinocytes (Goyette et al, 2000). The precise mechanism of transrepression of AP-1 by RA is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…An AP-1 complex consisting of JunB and Fra-1 or another JunB-or Fra-1-containing complex appears to be one target of transrepression by RA. A recent study using RAR null keratinocytes revealed that RAR is essential for the transrepression of AP-1 activity by RA (Goyette et al, 2000). RARg plays a major role in AP-1 transrepression by RA in JB6 cells (Rudd et al, 1993).…”
Section: Ra Targets the Transcriptional Activation Of Full-length Junmentioning
confidence: 99%